Analisis Dinamika Emosi, Perilaku, dan Motivasi Belajar Siswa Kecanduan Gim Daring dan strategi Penanganannya ( Studi Kasus di MA Futuhiyyah Kudu Semarang) - Syafarudin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to analyze the impact of online game addiction on students’ emotional dynamics, behavior, and learning motivation, as well as to identify the handling strategies implemented at MA Futuhiyyah Kudu Semarang. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that online game addiction significantly affects three main aspects. First, the emotional aspect, characterized by emotional instability, irritability, and the emergence of anxiety when not playing. Second, the behavioral aspect, which includes a decline in discipline, tardiness, disrupted sleep patterns, procrastination, and low participation in social and religious activities. Third, the learning motivation aspect, which decreases both intrinsically and extrinsically, with students showing more interest in in-game achievements than in academic performance. The handling strategies implemented include solution-focused individual counseling, digital literacy socialization, restrictions on mobile phone use at school, integration of Islamic moderation values into learning, and the provision of alternative activities. Nevertheless, their effectiveness remains limited due to a lack of counseling resources, low parental understanding, and student resistance. This study recommends a holistic approach involving synergy between teachers, parents, and the social environment, with an emphasis on self-control and balanced use of technology in accordance with Islamic values